2018
DOI: 10.21037/jtd.2018.02.51
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy alcohol use is associated with postoperative complications in veterans undergoing lung resection

Abstract: Background: Lung resections carry a significant risk of complications necessitating the characterization of peri-operative risk factors. Unhealthy alcohol use represents one potentially modifiable factor. In this retrospective cohort study, the largest to date of lung resections in the Veterans Health Administration (VHA), we examined the association between unhealthy alcohol use and postoperative complications and mortality. Methods: Veterans Affairs Surgical Quality Improvement Program data recorded at 86 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(58 reference statements)
0
6
0
Order By: Relevance
“… 49 By contrast, squamous cell carcinoma was associated inversely with any level of alcohol drinking. Alcohol dependency also has been associated with an increased risk of postoperative complications in patients undergoing lung cancer surgery 50 , 51 ; however, the results are conflicting regarding the effect on mortality. 50 , 51 , 52 , 53 Taken together, efforts aiming to reduce excessive alcohol consumption and to prevent dependency may have the potential to decrease morbidity and mortality in patients with lung cancer, particularly among men.…”
Section: Discussionmentioning
confidence: 99%
“… 49 By contrast, squamous cell carcinoma was associated inversely with any level of alcohol drinking. Alcohol dependency also has been associated with an increased risk of postoperative complications in patients undergoing lung cancer surgery 50 , 51 ; however, the results are conflicting regarding the effect on mortality. 50 , 51 , 52 , 53 Taken together, efforts aiming to reduce excessive alcohol consumption and to prevent dependency may have the potential to decrease morbidity and mortality in patients with lung cancer, particularly among men.…”
Section: Discussionmentioning
confidence: 99%
“…While the cutoffs and metrics for measuring alcohol consumption may be heterogenous between studies, it was consistently identified as a key modifiable risk factor for postoperative morbidity. 32 A VASQIP analysis of veterans undergoing lung resection by Graf et al 33 also found alcohol consumption to be associated with increased postoperative pneumonia. While that study examined both open and VATS lung resection cases, it addressed the same veteran population and adds emphasis to the predictive risk that alcohol consumption carries.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have linked preoperative alcohol consumption with postoperative complications. [32][33][34] In a 2013 meta-analysis, Eliasen et al 32 reported that preoperative alcohol consumption was significantly associated with overall postoperative morbidity, including pulmonary complications. While the cutoffs and metrics for measuring alcohol consumption may be heterogenous between studies, it was consistently identified as a key modifiable risk factor for postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly greater proportion of patients who abuse alcohol are also smokers, when compared to the general population. The authors showed that unhealthy alcohol use with smoking was associated with an increased risk of postoperative complications when compared to patients who did not smoke (116). This points to the synergistic role of alcohol and smoking.…”
Section: Alcohol Dependencymentioning
confidence: 98%